Etnobotânica das plantas medicinais com potencial anti-inflamatório usadas pelos moradores da comunidade ilha Trambioca, Barcarena, Pará - CONCEIÇÃO, Suzete Fonseca (2019)
The Brazilian flora has a wealth of medicinal plants and represent a remarkable source of bioactive principles used in health care and prevention of human affections. In this context, the objective of this work was to conduct an ethnobotanical survey of the medicinal plants with anti-inflammatory potential used by the residents of Trambioca island, Barcarena, Pará. The collaborators were selected by a non-probabilistic "snowball" approach and data collection a semi-structured questionnaire was applied. A total of 66 ethnoespecies were identified, of which 51 were identified at the species level, distributed among 36 genera and 25 families. The best represented families were Lamiaceae (7 species), Euphorbiaceae (4 species), Meliaceae (3 species), Phyllantaceae (3 species), Asteraceae, Bignoniaceae, Rutaceae, Poaceae, Verbenaceae and Zingiberaceae (2 species each). Among these species 15% were used to treat inflammatory diseases, based on traditional knowledge and acquired orally.